2021
DOI: 10.3390/vaccines9020142
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Viral-Like Particle Candidate Vaccine Against Novel Variant Infectious Bursal Disease Virus

Abstract: Infectious bursal disease (IBD), an immunosuppressive disease of young chickens, is caused by infectious bursal disease virus (IBDV). Novel variant IBDV (nVarIBDV), a virus that can evade immune protection against very virulent IBDV (vvIBDV), is becoming a threat to the poultry industry. Therefore, nVarIBDV-specific vaccine is much needed for nVarIBDV control. In this study, the VP2 protein of SHG19 (a representative strain of nVarIBDV) was successfully expressed using an Escherichia coli expression system and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Wang et al reported that the IBDV SH619-VLP vaccine induced comparatively lower antibody titers than the commercial vaccine [33]. Our ndings also demonstrated signi cantly high IgY titers after two weeks of vaccination.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Wang et al reported that the IBDV SH619-VLP vaccine induced comparatively lower antibody titers than the commercial vaccine [33]. Our ndings also demonstrated signi cantly high IgY titers after two weeks of vaccination.…”
Section: Discussionsupporting
confidence: 65%
“…Therefore, the IBDV major capsid protein VP2 is utilized for developing diagnostics and novel subunit vaccines [12,14]. Recent studies used Escherichia coli [7,33], Lactococcus lactis [34], and plant [14] expression systems to express IBDV rVP2 based virus-like particles and had a molecular mass of more than 40 kDa. This study elaborated the diagnostic and immunogenic potential of a truncated 19 kDa rVP2 protein.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study showed that commercial vvIBDV vaccines provide only 50% protection against nvIBDV [32]. It seems that broad crossprotection of nvIBDV vaccines is provided by its universal neutralizing epitopes [31]. Nevertheless, its cross-neutralizing activity was not high against vvIBDV genotypes after immunization by nvIBDV vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Given that multiple IBDV genotypes are epidemic in China simultaneously, crossprotection is a particularly important factor in the vaccine development [30]. A recent study showed that the recombinant nvIBDV VP2 (466 aa) protein expressed by E. coli provides 100% protection against both nvIBDV and vvIBDV genotypes [31]. The results are encouraging, but whether the nvIBDV vaccine can provide cross-protection against genotypes other than vvIBDV remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…This finding correlated with the fact that G2 variants were isolated from poultry flocks immunized with commercial intermediate vaccines [ 14 , 19 , 35 , 36 ]. Several attempts to developing vaccine candidates against G2d variants has been done [ 37 , 38 ]. Moreover, some commercial recombinant vaccines have been reported to induce protection against a wide range of IBDV strains, including G2 variants [ 39 ].…”
Section: Discussionmentioning
confidence: 99%